2016
DOI: 10.1080/13543776.2017.1236918
|View full text |Cite
|
Sign up to set email alerts
|

RORγ antagonists and inverse agonists: a patent review

Abstract: The transcription factor RORγ plays a critical role in the expression of pro-inflammatory cytokine interleukin IL-17 and is therefore an attractive target for the treatment of inflammatory diseases. Interest in this molecular target has been heightened by the advancement of orally and topically administered RORγ modulators into clinical trials. Areas covered: The present review seeks to summarize published patent applications from assignee companies that have disclosed Investigational New Drug (IND) filings fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Another possibility is that Mo-MDSCs downregulate IL-17A levels in circulation [31]. e transcription factor ROR-c plays a critical role in the expression of proinflammatory cytokine IL-17 in patients with psoriasis [32] and is, therefore, an attractive target for the treatment of psoriasis [33]. In the current study, we found the ROR-c mRNA levels were significantly increased in the PBMCs of psoriasis patients when compared to controls.…”
Section: Discussionsupporting
confidence: 52%
“…Another possibility is that Mo-MDSCs downregulate IL-17A levels in circulation [31]. e transcription factor ROR-c plays a critical role in the expression of proinflammatory cytokine IL-17 in patients with psoriasis [32] and is, therefore, an attractive target for the treatment of psoriasis [33]. In the current study, we found the ROR-c mRNA levels were significantly increased in the PBMCs of psoriasis patients when compared to controls.…”
Section: Discussionsupporting
confidence: 52%
“…A number of ROR␥ inverse agonists are under clinical development based on the ability of ROR␥ to suppress T h 17 cell development and function (14). Our group, as well as the Littman group (13), were the first to identify ROR␥ inverse agonists and characterize their ability to suppress T h 17 cell development/function and reduce the severity of autoimmune disease in rodent models (7).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that targeting inhibition of ROR␥ activity with inverse agonists is an effective method for suppressing T h 17 cell differentiation and function as well as treatment of autoimmune diseases in rodent models (7,(11)(12)(13). Several of these ROR␥ inverse agonists are now being evaluated in clinical trials to treat autoimmune diseases such as psoriasis (14). Beyond T h 17 lymphocytes, ROR␥ is also expressed in innate immune cells, such as macrophages and natural killer cells, suggesting a wider role for ROR␥ beyond T h 17 cell differentiation and function in regulation of immunity.…”
Section: Rar-related Orphan Receptor ␥ (Ror␥) Is a Nuclear Receptor Tmentioning
confidence: 99%
“…[10] Overviews summarizing the current knowledge of structural biology aroundR ORgta gonists, antagonists, and inverse agonists (including orthosteric and allosteric binders)h aveb een published recently. [10] Overviews summarizing the current knowledge of structural biology aroundR ORgta gonists, antagonists, and inverse agonists (including orthosteric and allosteric binders)h aveb een published recently.…”
mentioning
confidence: 99%
“…In the last few years several companies have patented chemicals eries, mainly to discovera nd optimize inverse agonists, for both oral and topicala dministration. [10] Overviews summarizing the current knowledge of structural biology aroundR ORgta gonists, antagonists, and inverse agonists (including orthosteric and allosteric binders)h aveb een published recently. [4,11] Herein we report eight new X-ray structures for natural and synthetic compounds including selected examples from the patent literature.…”
mentioning
confidence: 99%